Kaleidoscope heart - Mazzola, Rosetta (Revue canadienne de l’éducation médicale, 2019)
I am an enthusiastic amateur photographer, taking great pleasure in capturing landscapes but also dabbling in portrait and still life photography. This image was inspired by my daily bicycle commute to and from UBC's Point Grey campus during my first semester of medical school in the fall of 2016. Every day, I cycled through the ever-changing landscape of Vancouver. While we were studying cardiology, in my mind’s eye, the colourful leaves falling from the trees formed the chambers and vessels of a heart. This playful fantasy reminded me of the importance of maintaining an open mind in recognizing patterns when diagnosing patients in medicine.